Symposium 5: Phenomenography and elearning in art and design - Souleles, Nicos (Proceedings of the International Conference on Networked Learning, 2012)
The purpose of this paper is to elaborate on how phenomenography was used as part of an extensive study in the under-researched area of elearning in art and design in Higher Education (HE). The purpose of the original study was to identify the perceptions and practices of lecturers in undergraduate art and design disciplines, as well as the unique characteristics and challenges of the sector vis-à-vis elearning. In this paper, references are made to some of the limited studies of elearning and ICT implementation in art and design. This highlights the need for further research and supports the position adopted by this paper that phenomenography is ideally suited for under-researched areas of investigation. The paper refers to some of the research outcomes in the context of reflecting upon and elaborating on the research methodology per se and the challenges and benefits of using phenomenography to investigate elearning in art and design. Consistently with the phenomenographic approach to research, the original study pursued a second-order perspective, i.e. through a qualitative analysis of semi-structured interviews the research dealt with people’s experiences of aspects of the world. Subsequently, the paper addresses the main tenets and critiques of the research methodology and the overall process it entails. It addresses how phenomenography facilitates the identification, description and categorization of perceptions and practices for the creation of a final outcome space that is manifested as a topology of inter-related categories or groupings of the perceptions and practices identified through semi-structured interviews. The paper elaborates on the main qualitative and quantitative critiques of phenomenography, as well as issues of validity and objectivity. The latter entails dealing with the concept of bracketing and the relationship between the researcher and the process of acquiring and interpreting the data through phenomenographic methods. Finally, this paper concludes that the contribution of phenomenography was invaluable in revealing the spectrum of challenges vis-à-vis elearning in art and design, and in opening up this specific area of study to further research.